Clinical diagnostic and therapeutic aspects of 221 consecutive anorectal Chlamydia trachomatis and Neisseria gonorrhoeae sexually transmitted infections among men who have sex with men - J. Lourtet Hascoet (International Journal of Infectious Diseases, 2018)
Objectives: Proctitis caused by Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) are known as sexually transmitted infections (STI). This study describes their clinical, diagnostic and therapeutic aspects. Methods: Between 01/2013-03/2015, all MSM consulting for proctitis at proctology Institute-Saint-Joseph’s Hospital, Paris, were included. Demographic, past-medical history, STI status and medical treatment were collected. Detection of CT/NG was performed by Transcription-Mediated Amplification (TMA) and antimicrobial susceptibilities for Ng by agar diffusion method. Results: On 441 rectal samples collected, 221 (50.1%) were positive: 109 Ct (49.3%), 70 Ng (31.7%), 42 positive for both etiologies (19%). Among Ng infections, no resistance was detected to azithromycin and ceftriaxone. However, 84 strains (43.2%) were resistant to fluoroquinolones. More than one episode was diagnosed for 10 (5.1%) and 12 (6.2%) patients with CT and NG infections respectively. Anal abscesses were found for 27 (13.9%) patients, and 14 (7.2%) of them underwent surgery for anal fistula. Conclusions: The prevalence of CT/NG anorectal infections described is high on symptomatic patients, and a significant level of abscess was reported. These results confirm the interest of the association of recommended antibiotics excluding quinolones. Prospective studies would be relevant on complicated forms of anorectal infections.